2012
DOI: 10.1162/jocn_a_00198
|View full text |Cite
|
Sign up to set email alerts
|

Distinct EEG Amplitude Suppression to Facial Gestures as Evidence for a Mirror Mechanism in Newborn Monkeys

Abstract: At birth, human infants and newborns of other primate species demonstrate the capacity to attend and to respond to facial stimuli provided by a caregiver. Newborn infants are also capable of exhibiting a range of facial expressions. Identification of the neural underpinnings of these capacities represents a formidable challenge in understanding social development. One possible neuronal substrate is the mirror-neuron system assumed to activate shared motor cortical representations for both observation and produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
107
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 84 publications
(118 citation statements)
references
References 37 publications
8
107
1
2
Order By: Relevance
“…Therefore, under the current experimental conditions, this frequency band could be considered an indirect correlate tapping the activity of the mirror mechanism. Recent work in newborn monkeys has shown that lower frequency bands recorded over frontal electrodes are suppressed during the observation and execution of facial gestures [40]. However, the frequencies sensitive to this set of stimuli were within the 5-6 Hz band; similar to the human alpha in infancy and consistent with developmental findings of the human infant mu rhythm.…”
Section: Discussionsupporting
confidence: 78%
“…Therefore, under the current experimental conditions, this frequency band could be considered an indirect correlate tapping the activity of the mirror mechanism. Recent work in newborn monkeys has shown that lower frequency bands recorded over frontal electrodes are suppressed during the observation and execution of facial gestures [40]. However, the frequencies sensitive to this set of stimuli were within the 5-6 Hz band; similar to the human alpha in infancy and consistent with developmental findings of the human infant mu rhythm.…”
Section: Discussionsupporting
confidence: 78%
“…First, the stimuli in the present study involved relatively simple motor activities that occurred in a neutral context. Although mu suppression is sensitive to observing emotional facial expressions in humans (Moore, Gorodnitsky, & Pineda, 2012), and even facial gestures in newborn monkeys (Ferrari et al, 2012), it remains to be determined how schizophrenia patients would perform on mu suppression tasks involving more complex socioemotional stimuli. Second, studies using other methods have suggested that mirroring-related processes are not fully intact in schizophrenia.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, we hypothesize that the mirror neuron system is a potential candidate for mediating some of the social effects of oxytocin. Recently, it was reported that, during the observation and imitation of facial gestures, such as LPS, specific brain rhythms (the mu rhythm) are desynchronized (71). These EEG changes may reflect the activity of cortical parietal-frontal networks, which are part of the mirror neuron system (72).…”
Section: Discussionmentioning
confidence: 99%